The Role of Village Government in Administrative Service Governance in Tenilo Village, Tilamuta District - Mukdin, Novita B; Polinggapo, Jefri; Paweni, Lisnawati; Walahe, Dewi; Tabo, Sarfan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The role of village government in improving the quality of administrative services at the village office is part of the effort to realize professional public services that are oriented toward community satisfaction. The village government acts as both a policymaker and a service implementer, responsible for providing an orderly, fast, and transparent administrative system. This study was conducted at the Tenilo Village Office, Tilamuta District. The purpose of this research is to determine the extent to which the village government plays a role in improving the quality of administrative services at the Tenilo Village Office, Tilamuta District, Boalemo Regency. This research employs a qualitative method. Data collection techniques include observation, interviews, and documentation. The data sources consist of primary and secondary data. The data analysis technique used is descriptive qualitative analysis, which includes data reduction, data presentation, and conclusion. The results of the research conducted at the Tenilo Village Office, Tilamuta District, indicate that the government has played an active role in improving the quality of administrative services. However, there are still inhibiting factors in improving service quality. Internal constraints include: (1) service facilities, (2) skills and competencies, and (3) budget limitations. Meanwhile, external constraints include: (1) community participation.